PENGEMBANGAN ELEKTRONIK MODUL (E-MODUL) AKUNTANSI DASAR UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA (Studi Pengembangan e-modul) Akuntansi Dasar Pada Kelas X SMK Negeri 2 Lahat) - Maryani N Maryani N (UNIB Press, 2020)
This research aims:1)Development of e-accounting modules that can facilitate the learning prosess, 2)Describe the feasibility of developing an e-module of accounting on the basis of exspert tests and tests tobe used in learning prosess, 3)Describe how electronics module can improve student achievement. This research main goal is to develop electronic modules or modules that can help students in learning because they can use a laptop and also smarphone (HP). The module development prosess uses sigil application for manufacturing processand to read it using EPUB reader using Azardi for laptop and easily for smartphone (HP). This development is expected to guide students with digital learning patterns 4.0. Becauuse the materialand evaluasion can be adjustes to the learning abitlities of each student. This e-module is expected to be able to: 1) Help students learn by themselves without the presence of teacher, 2) Help teacher have digital learning suggestions in the form of electronic module (e-module), 3) One of the references for learning accouting digitally. This development researh used ADDIE methid (Analyze, Design, Development, Implematation and Evaluation). After validation the e- module will try to the student in basic area and in the widht area. To see if test the e- module. The result the e-module can be used in learning proses.